Virus detection by PCR following vaccination of naive calves with intranasal or injectable multivalent modified-live viral vaccines. (September 2017) - Walz, Paul H.; Newcomer, Benjamin W.; Riddell, Kay P.; Scruggs, Daniel W.; Cortese, Victor S.
We evaluated duration of PCR-positive results following administration of modified-live viral (MLV) vaccines to beef calves. Twenty beef calves were randomly assigned to either group 1 and vaccinated intranasally with a MLV vaccine containing bovine alphaherpesvirus 1 (BoHV-1), bovine respiratory syncytial virus (BRSV), and bovine parainfluenza virus 3 (BPIV-3), or to group 2 and vaccinated subcutaneously with a MLV vaccine containing bovine viral diarrhea virus 1 and 2 (BVDV-1, -2), BoHV-1, BRSV, and BPIV-3. Deep nasopharyngeal swabs (NPS) and transtracheal washes (TTW) were collected from all calves, and whole blood was collected from group 2 calves and tested by PCR. In group 1, the proportions of calves that tested PCR-positive to BVDV, BoHV-1, BRSV, and BPIV-3 on any sample at any time were 0%, 100%, 100%, and 10%, respectively. In group 1 calves, 100% of calves became PCR-positive for BoHV-1 by day 3 post-vaccination and 100% of calves became PCR-positive for BRSV by day 7 post-vaccination. In group 2, the proportions of calves that tested positive to BVDV, BoHV-1, BRSV, and BPIV-3 on any sample at any time were 50%, 40%, 10%, and 0%, respectively. All threshold cycle (Ct) values were >30 in group 2 calves, irrespective of virus; however, Ct values <25 were observed in group 1 calves from PCR-positive results for BoHV-1 and BRSV. All calves were PCR-negative for all viruses after day 28. Following intranasal MLV viral vaccination, PCR results and Ct values for BRSV and BoHV-1 suggest that attempts to differentiate vaccine virus from natural infection is unreliable.